ANALISIS KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA SISWA KELAS VIII MTS AT-TAQWA BEKASI PADA MATERI LINGKARAN - Wenda Nur Kawiyah; Huri Suhendri; Edward Alfin (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2022)
This study aims to describe the level of ability to understand mathematical concepts of students of class VIII MTs At-Taqwa on circle material. The research method used is a descriptive qualitative method. The subjects of the study were students of class VIII-2 MTs At-Taqwa Bekasi totaling 26 people and one class VIII mathematics teacher. From the research subjects will be selected using purposive sampling techniques. Furthermore, the ability to understand mathematical concepts will be analyzed according to the test results and interview results of the selected 3 students. From each of the students who have been selected represent the high, medium and low group categories. The results showed that the level of understanding of mathematical concepts in the high group category was 4 people or 16%, the level of understanding of mathematical concepts in the medium category was 16 people or 64%, and the level of understanding of mathematical concepts in the low category was 5 people or 20%. While the achievement of indicators is different for each indicator, namely the percentage for each indicator is as follows: only 90.6% of students are able to meet the indicators of re-state the concept, 32.3% of students who are able to meet classifying indicators / grouping objects according to certain traits according to their concept, 14.5% of students who are able to meet the indicators develop the concepts that have been owned, and 11.5% of students who are able to meet the indicators  use and utilize and select specific procedures or operations and apply them to troubleshooting